2019
DOI: 10.1029/2018jb016778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induced Stress on Seismic Waves: Validation Based on Ab Initio Calculations

Abstract: When a continuum is subjected to an induced stress, the equations that govern seismic wave propagation are modified in two ways. First, the equation of conservation of linear momentum gains terms related to the induced deviatoric stress, and, second, the elastic constitutive relationship acquires terms linear in the induced stress. This continuum mechanics theory makes testable predictions with regard to stress‐induced changes in the elastic tensor. Specifically, it predicts that induced compression linearly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Firstly, no matter its functional form, A 1 can be shown to possess all the classical elastic symmetries, as required by eq.(2.55). Secondly, given that it is explicitly linear in the stress-perturbation, this theory is superficially rather close to those of Dahlen (1972b), Dahlen & Tromp (1998), Tromp & Trampert (2018) and Tromp et al (2019), discussed in Section 1. There are some important differences, though.…”
Section: Linearisationmentioning
confidence: 54%
See 3 more Smart Citations
“…Firstly, no matter its functional form, A 1 can be shown to possess all the classical elastic symmetries, as required by eq.(2.55). Secondly, given that it is explicitly linear in the stress-perturbation, this theory is superficially rather close to those of Dahlen (1972b), Dahlen & Tromp (1998), Tromp & Trampert (2018) and Tromp et al (2019), discussed in Section 1. There are some important differences, though.…”
Section: Linearisationmentioning
confidence: 54%
“…Because the theories lead to distinct observable behaviour, mineral physics experiments or ab initio calculations have the potential to distinguish between them (e.g. Tromp et al 2019). Nonetheless, it is not clear to the present authors that the resolution of this issue lies simply in finding a correct choice for these constants.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The influence of initial stress on the nature of the propagation of elastic waves in rocks and sands has been experimentally studied [Li, Tao, 2015;Teachavorasinskun, Pongvithayapan, 2016]. Another interesting variant of study of effects of initial stress is suggested [Tromp et al, 2019]. The main linear and nonlinear physico-mechanical properties of the geological medium, the kinematic parameters of elastic waves, and the main components of the stress tensor are analytically related to each other in acousto-elastic correlations in the NLA.…”
mentioning
confidence: 99%